Challenges and opportunities facing zinc anodes for aqueous zinc-ion battery - Boyu Li; Yuetao Ma; Jiabin Ma; Likun Chen; Yang Zhao; Man-Chung Tang (Energy Materials and Devices)
Rechargeable aqueous zinc-ion batteries (ZIBs) have gained attention as promising candidates for next-generation large-scale energy storage systems due to their advantages of improved safety, environmental sustainability, and low cost. However, the zinc metal anode in aqueous ZIBs faces critical challenges, including dendrite growth, hydrogen evolution reactions, and corrosion, which severely compromise Coulombic efficiency and cycling stability, hindering their broader adoption. This review first explores the fundamental mechanisms underlying these challenges and then examines current strategies to address them, focusing on structural design, surface modifications, electrolyte optimization, and alloying treatments. Finally, potential future directions are discussed, outlining a pathway toward achieving high-performance aqueous ZIBs.